Efficacy of intranasal olopatidine hydrochloride as an add on therapy in mild to moderate allergic rhinitis - Sahayam J., Sam Anbu; K., Vasanthira (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Treatment with intranasal olopatidine hydrochloride spray is proposed for patients with chronic perennial and seasonal rhinitis. Hence we compared the efficacy of intranasal mometasone furoate as an add-on therapy with existing standard treatment in a randomized, open label comparative study. Methods: A prospective, randomized, single blinded, comparative study in patients with chronic perennial and seasonal rhinitis. Patients were divided into two groups to receive intranasal olopatidine therapy and intranasal saline plus existing standard treatment with levocetrizine and vitamin C orally. Improvement in symptoms like nasal obstruction, nasal discharge, sneezing, nasal itching, itching of eyes, watering of eyes were assessed by a questionnaire at 2, 4, 6 and 8 weeks and by a reduction of eosinophil count in blood and nasal smear examination at baseline and 8 weeks. Results: At the end of 8 weeks the percentage reduction of nasal obstruction in olopatidine hydrochloride and saline were 93.1% and 36.07% respectively, rhinorrhoea was 90.34% and 36.42%, nasal itching was 85.76% and 41.37% sneezing symptoms were 89.6% and 37.86%, itching in the eyes was 94.6% and 44.05% and watering in the eyes were 87.1% in group A and 38.07% in group B. At the end of 8 weeks, there was reduction in absolute eosinophil count and it attributed to 57.5% in olopatidine hydrochloride and 11.9% in saline group and reduction in nasal smear count scoring was 60.7% and 18.2% respectively. Conclusions: Intranasal olopatidine hydrochloride is highly effective, in the treatment of allergic rhinitis.